The difference of saline and sterile water for tetracycline hydrochloride solvents in cementum demineralization - Shinta Ferronika; Ahmad Syaify; Dahlia Herawati (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2016)
Background: The root cementum demineralization is an important step in regenerative periodontal therapy to smear layer removal on the root surface. Smear layer on the root surface becomes a barrier of the new attachment between periodontal tissues with the root surface. The use of tetracycline capsules as root surface demineralizing agent cannot be applied directly on the root surface and solvents such as saline or sterile water are needed. Purpose: The aim of this study was to determine differences between sterile water and saline solvent for tetracycline HCl (tetra HCl) as a cementum demineralization. Method: In this study the specimens were divided into three groups: a control, tetra HCl dissolved in saline, and tetra HCl dissolved in sterile water. Application using burnishing method for 3 minutes. Samples were dehydrated with ethanol series of 30% to 100%. Results of the root demineralization observed by scanning electron microscopy (SEM). Statistical analysis was performed using the Kruskal-Wallis followed by a Mann-Whitney nonparametric test. Result: Upon statistical analysis showed that the sterile water as a solvent of tetra HCl is more effective in smear layer removal and collagen structure exposure in the cementum. Conclusion: Tetra HCl dissolved in sterile water was found to be the best root cementum demineralization agent.